‘Of a Human Satellite’: Cassius Clay/Muhammad Ali in Cold War Finnish Television Culture, 1960–1965 - Salmi Hannu; Heiskanen Benita (Routledge, 2022)
This article discusses the reception of Cassius Clay/Muhammad Ali in Finnish media from 1960 to 1965, during the emergence of satellite broadcasting networks. The focus is especially on his two matches against Sonny Liston in 1964 and 1965, which had particular cultural and political resonance in Finland. Alongside other European sports fans, Finns were able to follow the bouts via satellite broadcasts, demonstrating not only the transnational possibilities of television but also the supposed technological supremacy of the West. The article is based on materials of the Finnish Broadcasting Company’s Radio and Television Archive and press coverage of Clay/Ali. The article argues that the Clay/Ali-Liston fights in Finland are best understood within the context of the Cold War, with the country itself being rapidly modernized after World War II. Within this geopolitical setting, the Clay/Ali-Liston boxing matches served as cultural vehicles in the broader Cold War debates, as the satellite broadcasts and other media activities helped to build Ali’s transnational fame and, in so doing, his globalization.